Emergency Contraception: Knowledge and Attitudes of Family Physicians of a Teaching Hospital, Karachi, Pakistan - Abdulghani, Hamza M; Karim, Syed I; Irfan, Farhana (Journal of Health, Population and Nutrition, 2009)
This study was conducted to assess the knowledge of family medicine providers and their attitudes towards emergency contraception in a teaching hospital in Karachi, Pakistan. A 21-item questionnaire containing the demographic profile of respondents and questions concerning knowledge of and attitudes towards emergency contraception was distributed among participants. In total, 45 interviews were conducted, with a response rate of 100%, with faculty physicians (33%), residents (27%), medical officers (40%), 36% male and 64% female physicians; of them, the majority (64%) were married. Although the large majority (71%) of the respondents reported considerable familiarity with emergency contraception, objective assessment revealed deficiencies in their knowledge. About 38% of the participants incorrectly chose menstrual irregularity as the most common side-effect of progestin-only emergency contraception pills, and only 33% answered that emergency contraception was not an abortifacient while 42% were unsure. Forty percent of the physicians prescribed emergency contraception in the past. The large majority (71%) of the physicians were familiar with emergency contraception, yet deficiencies in knowledge inaccuracies were identified. Barriers to its use were identified as ‘it will promote promiscuity' (31%), religious/ethical reasons (27%), liability (40%), teratogenicity (44%), and inexperience (40%). Overall attitudes regarding emergency contraception were positive; however, most (82%) physicians were unsatisfied with their current knowledge of emergency contraception, and there was a discrepancy between perceptions of physicians and actual knowledge. Interventions providing education to family physicians regarding emergency contraception is strongly recommended. Key words: Cross-sectional studies; Descriptive studies; Emergency contraception; Family physician; Family planning; Knowledge, attitudes, practice; Perceptions; Pakistan doi: 10.3329/jhpn.v27i3.3376 J Health Popul Nutr 2009 Jun;27(3):339-344